CONSIDERATIONS REGARDING THE SCOPE OF NOTIONS OF "EXCEPTIONAL SITUATIONS" - COMAN, Dumitru Ştefan (International Journal of Legal and Social Order, 2022)
From the beginning of the existence of state entities, measures were necessary to maintain and defend them against internal and external dangers. At the beginning, these measures were taken exclusively in military terms, later taking shape also in law and evolving simultaneously with state development. This evolution has outlined other risk factors, which can threaten the existence of the rule of law or the normal development of social, economic and political life. In order to combat these dangers, which can intervene unexpectedly, and to establish the state of normalcy as quickly as possible, the power factors in the state must take energetic and immediate measures. The content of exceptional states derives from those situations that are beyond the normal state of the rule of law, situations accompanied by serious dangers that may threaten its very existence or the normal development of social, economic and political life.